The Role of Entrepreneurial Marketing in Enhancing the Effectiveness of Strategic Decisions: An Analytical Study of the Opinions of Managers in First-Class Hotels in the City of Erbil - Kurdistan Region of Iraq - Mohammed Amin Ibrahim, Hunar; Noori Abdulla, Mahabat (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The study aimed to identify the role of entrepreneurial marketing by first-class hotel managers in the city of Erbil, in its dimensions (Customer Emphasis - Seizing the opportunities - Creativity in product service), in enhancing the effectiveness of strategic decisions and indicators to enhance their effectiveness (Appropriate decision - accept the decision - Decision quality). The general framework of the study is represented by the problem of the study. The questionnaire was used as a tool to collect the data. Then was distributed to managers, (106) questionnaires were distributed and the number of questionnaires returned (96) and the number of questionnaires valid for analysis was (93). Several tests were conducted before and after distributing the questionnaire to verify its validity, reliability and validity in measuring the study variables such as apparent validity and reliability (Cronbach’s alpha coefficient) And that through the use of statistical methods by the computer program (SPSS, V.21). The study adopted the descriptive-analytical method, Such as the study population in all first-class hotels in Erbil city and its count (14) five-star hotels. the results of the correlation analysis revealed about, the existence of positive, moral relationships at a high-level and influence between entrepreneurial marketing and the effectiveness of strategic decisions at the macro and micro levels, Based on the conclusions reached by the researcher, a set of proposals was formulated, the most important of which are: The necessity of emphasizing the understanding of customer needs in order to meet them in a way that satisfies the customer and not according to what the management sees in the hotels, is also The necessity the hotel management should focus on researching new service products for competitors and work on developing them.